2017
DOI: 10.1007/s12517-017-3031-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hydrogeochemical processes and groundwater quality for suitability of drinking and irrigation purposes: a case study in the Aosta Valley region, Italy

Abstract: The present study aims to discuss the hydrogeochemical processes in the Aosta Valley region and assess the quality of its groundwater for suitability of drinking and irrigation purposes. One hundred twenty-two samples were collected from the Aosta Valley region in the years 2007 and 2008 (61 per year), and analysed for pH, electrical conductivity, total dissolved solids (TDS), total hardness, major cations and anions. The pH of the samples in both years indicated a near-neutral to alkaline nature of the ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…This suggests that cation exchange processes are occurring, where a Ca 2+ ion is taken as the exchanger by a release of Na + ions [9,10,35]. Moreover, Ca 2+ showed a positive correlation (Figure 4a,b) with CO3 2− (0.785) and HCO3 − (0.772), indicating the dissolution and precipitation of calcite [9,74,[82][83][84][85]. A high positive correlation between Ca 2+ and NO3 − (0.87) suggests that the source of nitrate and calcium is the same (Figure 4c), and could be attributed to nitrate from agricultural fertilizers leaching to the aquifer [86].…”
Section: Correlation Among Variablesmentioning
confidence: 92%
“…This suggests that cation exchange processes are occurring, where a Ca 2+ ion is taken as the exchanger by a release of Na + ions [9,10,35]. Moreover, Ca 2+ showed a positive correlation (Figure 4a,b) with CO3 2− (0.785) and HCO3 − (0.772), indicating the dissolution and precipitation of calcite [9,74,[82][83][84][85]. A high positive correlation between Ca 2+ and NO3 − (0.87) suggests that the source of nitrate and calcium is the same (Figure 4c), and could be attributed to nitrate from agricultural fertilizers leaching to the aquifer [86].…”
Section: Correlation Among Variablesmentioning
confidence: 92%
“…WQI is an important tool in evaluating the overall quality of shallow groundwater, as it summarizes a large set of water quality data into a single value, enabling an effective understanding of the quality of shallow groundwater (Chen et al 2019;Hou et al 2016). WQI values have been used to study different water bodies and numerous results have been reported Soleimani et al 2018;Tiwari et al 2017). WQI is calculated in four steps:…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…Application of geographical information systems (GIS) provides spatial mapping, which gained immense popularity among the other data interpretation techniques. Its application in water resources becomes inevitable, and several researchers are using this method extensively in their studies [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%